Identification of maximal lactate steady state by a short lactate minimum test in walking - Puga, G. M.; Nakamura, F. Y.; Simões, H. G.; Sotero, R. C.; Zagatto, A. M. [UNESP]; Campbell, C. S.G. (Elsevier, 2021)
Objectives: The purpose of this study was to analyze the validity of a short Lactate Minimum test (LM) to assess the maximum lactate steady state (MLSS) during walking tests. Equipment and methods: Twelve healthy young participants performed LM on a treadmill at 5.5 km·h−1, with the intensity being incremented by inclination (%). Participants first performed a walking trial at 5.5 km·h−1 with 20% or 22% inclination until voluntary exhaustion. After 7 min of recovery an incremental test was initiated by using only 3 incremental stages that were selected based on the rate of perceived exertion (RPE). The LM intensity was identified as the lowest [bLac] during the incremental test, by using a visual inspection (LM3v) and applying a polynomial function of second order (LM3p). The MLSS intensity was also measured. Results: ANOVA showed no difference between the intensities (i.e., treadmill inclination) of MLSS (13.3 ± 2.2%), LM3 v (12.6 ± 1.6%), and LM3p (13.4 ± 1.3%). Conclusion: It was possible to identify the LM during walking by using 3 stages in most of the participants expressing the MLSS intensity with good agreement and correlation between them.
Identification de l’état durable de lactate maximal par un test minimum de lactate court à la marche
Keywords: Aerobic Fitness; Polynomial function; Rating of perceived exertion; Walking test